Thirty-eight years after: changes in the diet of the long-eared owl Asio otus in a protected area of NW Italy - Lorenzo Mazzocchi; Luca Canova (Rivista Italiana di Ornitologia - Research in Ornithology)
The diet of long-eared owls was studied by analyzing pellets collected in the winters of 1985 and 2021 in a protected areas of NW Italy. In 1985, the owl diet was dominated by the wood mouse Apodemus sylvaticus, birds (Ploceidae sp.), and the Savi’s vole Microtus savii; in 2021, the diet is dominated by the harvest mouse Micromys minutus, the wood mouse, and the bank vole Myodes glareolus. The shift in diet only partially reflects changes over time in the arable land surrounding the nature reserve. While the increase in the number of bank voles over 38 years can be explained by the increase in forest cover, the increase in the number of rice field mice contrasts with the reduction in their preferred habitats; the marshes have disappeared, the ditches have been reduced, and riparian vegetation has largely been removed. In addition, the most stable agro-ecosystems, such as poplar groves and meadows, have been largely replaced by intensive cereal and soybean crops. It is likely that improved harvesting and the expansion of intensive cultivation may partly explain some dietary shifts, such as the decline in birds, while the increase in harvest mice may be the effect of increased opportunistic predation on small populations surviving in suitable but fragmented habitats. As the harvest mouse is in decline throughout its range, natural and anthropogenic habitat changes may indirectly lead to increased predation on a threatened species and undermine its conservation.